When Double is not Twice as Much - Singer, Theresa M.; Groß-Hardt, Rita (Frontiers in Plant Science, 2011)
Gene and genome duplications provide a playground for various selective pressures and contribute significantly to genome complexity. It is assumed that the genomes of all major eukaryotic lineages possess duplicated regions that result from gene and genome duplication. There is evidence that the model plant Arabidopsis has been subjected to at least three whole genome duplication events over the last 150-200 million years. As a result, many cellular processes are governed by redundantly acting gene families. Plants pass through two distinct life phases with a haploid gametophytic alternating with a diploid sporophytic generation. This ontogenetic difference in gene copy number has important implications for the outcome of deleterious mutations, which are masked by the second gene copy in diploid systems but expressed in a dominant fashion in haploid organisms. As a consequence, maintaining the activity of duplicated genes might be particularly advantageous during the haploid gametophytic generation. Here, we describe the distinctive features associated with the alteration of generations and discuss how activity profiles of duplicated genes might get modulated in a life-phase dependent fashion to adjust redundancy levels in haploid and diploid tissues.